(untitled) (The Macau Ricci Institute Journal, 2019)
This paper examines the dynamic of spiritual friendship between the Jesuit painter Giuseppe Castiglione and three emperors: Kangxi, Yongzheng, and Qianlong, who reigned in China between 1662 and 1796. Paintings, historical reference and the poetic calligraphy which the emperor added with his own brush to Castiglione’s paintings, corroborate the notion of a deep friendship, one that is spiritual, in the way that spiritual friendship is defined and described by the 11th century Cistercian, Aelred of Rievaulx. The role of perspective, in both its technical and its spiritual connotations, is examined in terms of classical Chinese and western European traditions in relation to the deeper interior seeing of a spiritual friend. It is argued that Castiglione came to know the heart and mind of the emperor with such empathy that he is able to paint from that shared interiority, sharing affection, joy and even sorrow, beyond words, to suffuse spiritual experience within the work of painting, brush to silk, and for the gaze of the viewer.